On Artistic and Moral Wisdom in the Theodicy - Hare, John (Con-Textos Kantianos. International Journal of Philosophy, 2026)
This essay looks at a section of Kant’s ‘On the Miscarriage of All Philosophical Trials in Theodicy’, 8: 263-65, in which he makes two distinctions: first, that between artistic and moral wisdom, and second, that between doctrinal and authentic theodicy. The essay defends Kant’s vindication of Providence from a practical point of view. Kant argues that all the philosophical attempts at theodicy fail, but we can continue to hold onto the faith that the world is wisely governed if we restrict ourselves to moral, as opposed to artistic, wisdom and to authentic, as opposed to doctrinal, theodicy. Kant’s key move is negative, that the workings of the highest wisdom are beyond our experience and so beyond our insight; but where there is no theoretical veto, the practical interest prevails. The essay considers what this priority of the practical amounts to. Kant uses the geographical metaphor of ‘domains’ and argues that Reason, which has both theoretical and practical employments, has an interest in extending its territory, which requires theoretical reason to accept existence claims needed by practical reason even though these claims cannot be legitimated by theoretical reason from its own insight. The ‘authentic’ theodicy is God’s declaration within the practical employment of reason that there is a wisdom behind the creation and maintenance of the universe even though it is inscrutable to us and hidden.